Half-sib Progeny Evaluation in Pinus roxburghii Sargent - Sehgal, R. N.; Sankhyan, H. P.; Shrama, R. S. (Indian Forester, 2008)
Studies were undertaken to evaluate half-sib progenies in Pinus roxburghii Sargent at the age of about 12 years. Thirty three families were taken for study randomly out of a total of 58 families planted in the test n randomized complete block design to identify the promising selections to be used in future improvement programme. Eight growth characters viz., plant height, diameter at breast height, current year height increment, mean internodal length, specific gravity of branch wood, fresh weight of spur, dry weight of spur and per cent dry matter in spur were studied. Heritability (within family, half-sib family and individual tree basis) and genetic gains (family selection and within family selection) were also determined. Significant differences in all traits at half-sib and within families levels were observed except for the mean internodal length. Charet Mansu P4 (34) family showed overall best performance and may be used for further improvement work. Genetic gain of within family selection (GW) was found to be more than genetic gain of family selection (GF) for almost all characters. Most of the half-sib families exhibited better growth rates than predicted by yield tables for Pinus roxburghii at best sites which indicates that all the selected families are superior in growth traits.